Italian music at the Court of Queen Christina: Christ Church, Oxford, Mus. MS 377 and the visit of Vincenzo Albrici’s Italian ensemble, 1652–54 - Webber, Geoffrey (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1994)
-